Quantitative transportation assessment in curved canals prepared with an off-centered rectangular design system - Emmanuel João Nogueira Leal SILVA; Vania Cristina Gomes VIEIRA; Michele Dias Nunes TAMEIRÃO; Felipe Gonçalves BELLADONNA; Aline de Almeida NEVES; Erick Miranda SOUZA; Gustavo DE-DEUS (Sociedade Brasileira de Pesquisa Odontológica, 2016)
Abstract The purpose of this study was to assess the ability of an off-centered rectangular design system [ProTaper Next (PTN)] to maintain the original profile of the root canal anatomy. To this end, ProTaper Universal (PTU), Reciproc (R) and WaveOne (WO) systems were used as reference techniques for comparison. Forty clear resin blocks with simulated curved root canals were randomly assigned to 4 groups (n = 10) according to the instrumentation system used: PTN, PTU, R and WO. Color stereomicroscopic images of each block were taken before and after instrumentation. All image processing and data analysis were performed with an open source program (Fiji v.1.47n). Evaluation of canal transportation was obtained for two independent regions: straight and curved portions. Univariate analysis of variance and Tukey's Honestly Significant Difference test were performed, and a cut-off for significance was set at α = 5%. Instrumentation systems significantly influenced canal transportation (p = 0.000). Overall, R induced significantly lower canal transportation compared with WO, PTN and PTU (p = 0.000). The curved portion displayed superior canal transportation compared to the straight one (p = 0.000). The significance of the difference among instrumentation systems varied according to the canal level evaluated (p = 0.000). In its straight portion, R and WO exhibited significantly lower transportation than PTN; whereas in the curved portion, R produced the lowest deviation. PTU exhibited the highest canal transportation at both levels. It can be concluded that PTN produced less canal transportation than PTU and WO; however, R exhibited better centering ability than PTN.